Orthogonal vortex-rotor interaction: impact on rotor controls, blade flapping, thrust and power - Wall, B.G. van der (My University, 2018)
Rotors of vertical take-off and landing vehicles (main rotor, tail rotor, and propeller) are often subjected to interaction with vortices from other lifting devices. Interactions with vortices whose axes are essentially parallel to the rotor plane of rotation are widely investigated and understood, especially with respect to blade-vortex interaction (BVI) phenomena. Interactions of rotor blades with vortices oriented normal to the rotor disk were rarely investigated and this article focuses on this type of interaction, including the vortex impact on power required by the rotor. It is a fundamental study that is intended to contribute to future flight dynamics investigations.